Innovation in Providing Christian Religious Education in Youth Worship as a Learning Community - Gloria, Halce; Rajagukguk, Rioman Yesaya; Tasae, Priskila (PT FORMOSA CENDEKIA GLOBAL, 2024)
Church leaders, Christian youth organizations, church communities, and media/technology all contribute to bridging tradition with the aspirations of younger generations, fostering spiritual growth and meaningful relationships. This collaboration indeed enriches the religious experience for Christian youth through relevant and innovative approaches. Innovative worship awakens the spirit of the youth to come to worship God. Because, it always brings up new ideas for every worship program so that teenage youth are not easily bored. Worship that is carried out cannot be removed from the essence of worshiping God. Because, worshiping God, teenagers experience God personally. Young people can feel God's love and God's visit so that it can change the lives of teenage youth. During worship, young people actively express God's goodness in their worship and praise.